The Effect of Using Audio Visual on Students Writing Procedure Text at The Eighth Grade of SMPN 5 Kota Jambi In Academic Year 2018/2019 - Rosmaria Rosmaria; Kartika Dewi (Universitas Batanghari Jambi, 2019)
This research was done aimed at investigating if audio visual as a media more effect for the students skill in writing procedure text. The method of this research is quantitative. The population of the research is the eighth grade students of SMPN 5Kota Jambi. The researcher takes two classes of the eighth grade students as the sample from this research which were divided into two groups; experimental group (XIII A) and control group (XIII B). The XIIIA was taught by using Audio Visual as a media, while the XIII B was taught without Audio Visual as media. The instruments of collecting data are test: pre-test and post-test. To analyze the data, the researcher used experimental design. The mean in control class of pre test is 71,66 and mean post test 75,66. The mean in experimental class of pre test is 74,33 and the mean post test is 84,83. Based on the calculation of the statistical analysis, it is found that the value of t-test was 4,05 is higher than the value of t-table 1,69 at the degree freedom (df 30-1) = 29 and the level of confidence 0,05 with for that reason, the alternative hypothesis is accepted, the researcher could interpret that it was significantly effective to improve students writing procedure text using Audio Visual in SMPN 5 Kota Jambi. Keywords: Writing, Procedure text, Audio Visual.